2015
DOI: 10.1117/1.jbo.20.9.096006
|View full text |Cite
|
Sign up to set email alerts
|

Development of photostabilized asymmetrical cyanine dyes forin vivophotoacoustic imaging of tumors

Abstract: Photoacoustic imaging (PAI) contributes to tumor diagnosis through the use of PAI probes that effectively accumulate in tumors. Previously, we developed a symmetrical cyanine dye, IC7-1-Bu, which showed high potential as a PAI probe because of its high tumor targeting ability and sufficient in vivo PA signal. However, IC7-1-Bu lacks photostability for multiple laser irradiations, so we developed stabilized PAI probes using IC7-1-Bu as a lead compound. We focused on the effect of singlet oxygen (1O2) generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…to later develop asymmetrical derivatives of 8 functionalized with a 4‐nitrobenzyl alcohol group to serve as a triplet quencher moiety (Fig. 9 – 11 ) . It was found that these triplet quencher functionalized derivatives displayed in vitro PA signals that were equivalent to 8 while showing a 1.5‐fold increase in photostability.…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…to later develop asymmetrical derivatives of 8 functionalized with a 4‐nitrobenzyl alcohol group to serve as a triplet quencher moiety (Fig. 9 – 11 ) . It was found that these triplet quencher functionalized derivatives displayed in vitro PA signals that were equivalent to 8 while showing a 1.5‐fold increase in photostability.…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 99%
“…Molecular structures of the asymmetrical cyanine derivatives 9 – 11 reported by Onoe et al . with enhanced photostability relative to ICG ( 4 ) and 8 .…”
Section: Molecular Photoacoustic Contrast Agentsmentioning
confidence: 99%
“…Among them, PA imaging, which detects ultrasound thermoelastically generated from the optical absorbers irradiated with pulsed laser, has emerged as an attractive modality due to sensitive and high resolution imaging at a depth of several centimeters in vivo 2 3 . Currently, various PA signal-enhancing contrast agents (PA probes), including metallic nanoparticles 4 5 and fluorescence dyes 6 7 8 have been reported to aid in the diagnosis of tumors. However, these probes still remain in pre-clinical and clinical trials and are not in clinical use.…”
mentioning
confidence: 99%
“…In another example, Onoe et al . developed a symmetrical NIR cyanine dye for cancer imaging utilizing fluorescence and photoacoustic imaging 20 , but this probe degraded under high-energy laser pulses during imaging 21 .…”
Section: Introductionmentioning
confidence: 99%